Television Advertisement Comparative Analysis: The Use of Songs from Hot 100 Billboard Chart and Non-Hot 100 Billboard Chart - Muhammad, Rizki Maulana; Hudrasyah, Herry (Journal of Business and Management, 2016)
Abstract.The research is purposed to compare the cognitive component of attitude towards the advertising music in television advertisement. One advertisement uses song that had ever been in Hot 100 Billboard Chart as popular music while the another one uses song that had never been in Hot 100 Billboard Chart as non-popular music.Ã‚Â  The research takes review from a model of consumer response towards advertising music, approaches in television advertising, and popular music definition. The research scope is for Jakarta citizens aged 15 to 24 years old, uses copyrighted music as foreground, uses product-as-star approach, and the advertisement should be aired from March to June 2016. From the scopes mentioned above, two advertisements are selected to be treated as object in this research. The first one is Mizone advertisement that uses Dessert song by Dawin which had ever been in Hot 100 Billboard Chart. The second one is Close-up advertisement that uses Addicted to You song by Avicii which had never been in Hot 100 Billboard Chart. The data is gathered from quantitative research through online questionnaire and qualitative research from interview with expert. The data is analyzed through descriptive statistics and Mann-Whitney test. The result shows that using song that had ever been in Hot 100 Billboard Chart receives more favorable cognitive attitude towards advertising music, with significant difference (Sig. Value < 0.05) in level and persistence of attention to music, depth of processing to music, and remembered features of music available for association. This is in line with statement from interviewee that considers music popularity as a way to gain quick attention from audiences. Then, this research recommends practical implication for music producers to use songs from Hot 100 Billboard Chart, consider its relevancy, and also consider the airing period of an advertisement.Keywords : Television advertisement, cognitive component of attitude towards the advertising music, popular music, Hot 100 Billboard Chart